A STUDY ON THE EFFECT OF INTEREST AND PRIOR KNOWLEDGE ON READING COMPREHENSION AND TECHNIQUES TO ENHANCE PRIOR KNOWLEDGE IN READING COMPREHENSION TO THE 12TH FORM STUDENTS AT HIGH SCHOOL - Tran, Thi Yen (2021)
Reading and writing are two basic and critical skills from the very beginning of English language teaching process. However, it does not always perform the best outcome under the influence of various factors. The purpose of my study is to address and investigate how interest and prior knowledge affect reading comprehension and the techniques to enhance reading capability at the outset by means of reviewing major concepts of interest, prior knowledge and reading comprehension and techniques and related studies on the effect of interest and prior knowledge, the teaching English currently at high school. Subsequently, the paper continues with investigation involving the participation of 100 students for questionnaires of the general information on level of interest and prior knowledge. After defining three reading text ranging on level of interest and prior knowledge, reading test on three text was launched among 50 students who previously took part in questionnaires of the general information on level of interest and prior knowledge. Finally, 10 teachers were requested for information of questionnaire on techniques to enhance prior knowledge. The analyses of the collected data demonstrated a wide range of preference and the amount of knowledge among students as well as corroborate the influence in response to the first three proposed research questions. On the basis of these findings, the question four of the research were developed from researchers’ perspective in cooperation with the teachers’ questionnaire on the application of techniques to enhance prior knowledge. Some common and effective techniques had been brought to light to implement the best techniques to boost reading capacities